Kemampuan Fisiologi Tumbuhan Dalam Mengatasi Kekeringan - Mendrofa, Hepi Kardiani; Giawa, Benediktus; Duha, Fiorentina Agusmawati; Zendrato, Cahya Masaindah; Lase , Natalia Kristiani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Plants have two main mechanisms to cope with drought: avoidance and tolerance. Drought-avoidant plants usually accelerate their life cycle, while tolerant plants make osmotic adjustments and increase root growth. Stomatal closure, triggered by the hormone abscisic acid (ABA), plays an important role in reducing transpiration and maintaining cell turgor. This study highlights the importance of physiological adaptation in enhancing plant drought resistance.